Kinetics of microplastic generation from different types of mulch films in agricultural soil - Yang, Yang; Li, Zhen; Yan, Changrong; Chadwick, Dave; Jones, Davey L.; Liu, Enke; Liu, Qin; Bai, Runhao; He, Wenqing (The Science of the total environment, 2022)
Upon environmental weathering, plastic materials form smaller sized microplastics, of which the contamination in agricultural fields is of significant importance and increasing social concern. Plastic mulch films are considered a major source of agricultural soil microplastic pollution. However, the mechanism and kinetics of microplastic formation from plastic mulch films were rarely understood. In this study, the rate of microplastic generation from typical mulch films, such as oxodegradable, biodegradable, and conventional non-degradable (polyethylene, PE) mulch films, were quantified in soil under simulated UV irradiation. Results showed that microplastic formation was more rapid from biodegradable mulch film, followed sequentially by oxodegradable mulch film, white PE mulch film, and black PE mulch film. The kinetics of microplastic generation strictly followed the Schwarzchild's law, with exponential growth at indexes between 1.6309 and 2.0502 in the microplastic generation model. At a cumulative UV irradiation of 2.1 MJ/m2, the average quantity of microplastics released from biodegradable, oxodegradable, and white and black non-degradable mulch films were 475, 266, 163, 147 particles/cm2, respectively; with particle sizes largely distributed within 0.02–0.10 mm range. Concurrent increase in crystallinity and surface erosion of the mulch films were observed upon UV irradiation, which further determined the accessibility and activity of the materials to photo-oxidation (reflected as HI indexes), therefore played a critical role on the quantity and size ranges of microplastic debris. [Display omitted] •Kinetics of microplastic generation from mulch films were studied upon UV irradiation.•Biodegradable films were most rapid in microplastic formation, followed by oxo-film and PE film.•Kinetics of microplastic generation strictly followed the Schwarzchild's law.•Crystallinity and chemical composition are critical for the size and quantity of microplastics.•At cumulative UV exposure of 2.1 MJ/m2, 147–475 microparticles/cm2 could be released.